2013
DOI: 10.1186/cc12544
|View full text |Cite
|
Sign up to set email alerts
|

Augmented renal clearance in septic and traumatized patients with normal plasma creatinine concentrations: identifying at-risk patients

Abstract: IntroductionImproved methods to optimize drug dosing in the critically ill are urgently needed. Traditional prescribing culture involves recognition of factors that mandate dose reduction (such as renal impairment), although optimizing drug exposure, through more frequent or augmented dosing, represents an evolving strategy. Elevated creatinine clearance (CLCR) has been associated with sub-therapeutic antibacterial concentrations in the critically ill, a concept termed augmented renal clearance (ARC). We aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
195
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(221 citation statements)
references
References 48 publications
10
195
1
6
Order By: Relevance
“…In the critically ill, for instance, clearance could be elevated (e.g., 17.1 liters [18]) or similar/slightly higher (e.g., 13.8 liters/h [15,16] and 14.0 Ϯ 7.1 liters [17]) or may even be reduced (e.g., 3.6 liters/h [19] and 5.6 Ϯ 3.2 liters/h [12]) compared to healthy volunteers (13). It could be particularly high in those patients with burns and trauma (20). For example, a pharmacokinetic model for burn patients predicts elevated clearance of 16 liters/h for patients when CL CR is 130 ml/min and 20 ml/min when CL CR is 160 ml/min (21).…”
Section: Discussionmentioning
confidence: 98%
“…In the critically ill, for instance, clearance could be elevated (e.g., 17.1 liters [18]) or similar/slightly higher (e.g., 13.8 liters/h [15,16] and 14.0 Ϯ 7.1 liters [17]) or may even be reduced (e.g., 3.6 liters/h [19] and 5.6 Ϯ 3.2 liters/h [12]) compared to healthy volunteers (13). It could be particularly high in those patients with burns and trauma (20). For example, a pharmacokinetic model for burn patients predicts elevated clearance of 16 liters/h for patients when CL CR is 130 ml/min and 20 ml/min when CL CR is 160 ml/min (21).…”
Section: Discussionmentioning
confidence: 98%
“…In septic AKI patients, renal function was reported not to decline as low as expected, which could lead to underestimation of glomerular filtration rate and insufficient drug dosing [10]. This phenomenon is termed aug- mented renal clearance in which renal function for solution clearance is elevated more than expected by visible laboratory data in critically ill patients [11,12]. Therefore, more sensitive biomarkers such as the measured creatinine clearance are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Increased β-lactam clearance in patients with sepsis, but without organ dysfunction, can lead to subtherapeutic levels for significant periods. [14][15][16][17] CLcr should be routinely measured if there is doubt about the GFR and evidence that an 8-hour collection may be just as accurate as a 24-hour one. A recent prospective, singlecentre observational study of patients with VAP treated with doripenem or imipenem demonstrated a greater mortality and lower cure with CLcr >150 mL/min.…”
Section: Articlementioning
confidence: 99%